DEVELOPMENT OF PERFORMANCE SKILLS OF STUDENTS ON THE BASIS OF UZBEK FOLK INSTRUMENTS - Umurzakovna, Burkhonova Gulrux (Journal of Higher Education and Academic Advancement, 2024)
General Background: Music serves as a profound art form that enriches individual lives and fosters a conducive environment for personal and communal development. Specific Background: Its impact spans various domains, including labor, public affairs, and recreation, suggesting that music plays a crucial role in enhancing lifestyle quality. Knowledge Gap: Despite extensive recognition of music's benefits, there remains a lack of comprehensive understanding regarding its specific effects on creativity and individual maturation processes. Aims: This study aims to investigate the relationship between music appreciation and the development of creative abilities, while examining its influence on emotional well-being and aesthetic culture. Results: Preliminary findings indicate that engagement with music not only enhances creative expression but also significantly contributes to emotional resilience and aesthetic awareness. Novelty: This research introduces a nuanced perspective on the role of music as a catalyst for holistic personal development, emphasizing its dual capacity to evoke joy and reflect on the complexities of human emotion. Implications: The insights derived from this study underscore the importance of integrating music education and appreciation into personal development frameworks, suggesting that fostering musical engagement may serve as a vital component in cultivating creativity and emotional intelligence in individuals, thereby enriching societal cultural fabric.